Testicular involvement in mantle cell lymphoma: An analysis of 16 patients. - Samer Alkhalili; Dharmini Manogna; Hana Safah; Elizabeth Ellent; Walter Beversdorf; Ruby Arora; Nakhle S. Saba (Leukemia Research Reports, 2023)
Mantle cell lymphoma (MCL) with testicular involvement is a rare presentation and only a few cases have been described in the literature. We present a case of MCL with testicular involvement and the first analysis of all previously reported cases assessing trends in immunohistochemical features, prognostic indicators, and survival. Our data suggest that among all MCL, testicular MCL is more likely to present with aggressive features: blastoid/pleomorphic morphology, high Ki-67 proliferative index, and CNS involvement. Testicular MCL is also associated with shorter overall survival.